Abdominal sensing of substrate vibrations in insects - Alt, Joscha A.; Justus Liebig University Giessen (My University, 2025)
Mechanosensation is a universal sense and respective receptors are located in all body parts. For perception of substrate vibrations, highly specialized sensory organs have evolved. In insects, the legs serve as the primary sensory structures for vibration detection and contain specialized vibration receptors. However, many insect species also make contact with the substrate using their abdomen. Considering this and the presence of various chordotonal organs (COs) within the abdomen, we propose that the mechanosensitive abdominal chordotonal organs are also involved in the perception of substrate vibrations. To test this hypothesis, electrophysiological recordings were made of different abdomen-innervating nerves in two distinct insect species: Okanagana rimosa (Cicadidae) and Schistocerca gregaria (Orthoptera). In both the grasshopper and the cicada, the leg sensitivity is comparable to that of abdominal nerves, although depending on the frequency. Therefore, abdominal chordotonal organs are likely an important source for perception of substrate vibrations in insects, independent of the presence of legs. Additional information and the threshold values of the recordings are provided in the corresponding Excel file.
Are mechanosensitive abdominal chordotonal organs of Okanagana rimosa (Cicadidae) and Schistocerca gregaria (Orthoptera) involved in the perception of substrate vibrations
Keywords: animal physiology; vibration; neuronal recordings; sensory physiologiy; ddc:570